Advanced bioactive hydrogels for the treatment of myocardial infarction. Issue 41 (13th October 2022) - Lu, Yajie; Luo, Yuting; Zhu, Rui; Huang, Xiaowei; Bai, Shumeng
Abstract : Bioactive hydrogels exhibit physicochemical-responsive activities to repair infarcted myocardium and restore the cardiac function after myocardial infarction. Abstract : Myocardial infarction (MI) is the leading cause of cardiovascular disease-related deaths. Local ischemia and cardiomyocyte death lead to a series of pathological remodeling events of the infarcted extracellular matrix (ECM) that are significantly different from normal cardiac tissues. These pathological characteristics have inspired the development of microenvironment-responsive therapeutic strategies for MI. Bioactive hydrogels attract great attention because of their unique physicochemical features to induce specific biological responses upon interacting with cells, ECMs, and signal molecules. They exhibit physicochemical-responsive activities to regulate interactions between hydrogels and the biological system. Many bioactive hydrogels with intelligent properties have been used to repair infarcted myocardium and restore the cardiac function after MI. Current research studies ensure that bioactive hydrogels have a high clinical importance and application prospects. This review summarizes the advances of bioactive hydrogels in the field of on-demand treatment of MI and evaluates their key physicochemical characteristics. A range of bioactive hydrogels and their biomedical applications are discussed in repairing injured hearts and restoring cardiac functions, providing insights into the development of intelligent therapeutic approaches for MI.